The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.dsx.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of metabolic syndrome in the outcomes of colorectal cancer patients

Abstract: A B S T R A C TAims: Determine the influence of metabolic syndrome and its different components in the outcomes of colorectal cancer surgery at 30 days. Materials and methods: Prospective study that included all patients submitted to elective colorectal cancer surgery between August 2015 and August 2016 at Hospital de Braga. Clinical and laboratory parameters evaluated pre-operatively were: central obesity, blood pressure, fasting glucose, triglycerides levels and HDL cholesterol levels. Any complications duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
9
0
3
Order By: Relevance
“…Previous studies suggested that dyslipidemia was a newly identified risk factor in the survival of several cancers such as colorectal, breast, and prostate cancers [ 15 , 16 , 18 ]. Although one study demonstrated that preoperative HDL level was a predictor of HCC recurrence after liver resections [ 22 ]; recently, there were few studies that addressed the association between lipid profiles and the outcome of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that dyslipidemia was a newly identified risk factor in the survival of several cancers such as colorectal, breast, and prostate cancers [ 15 , 16 , 18 ]. Although one study demonstrated that preoperative HDL level was a predictor of HCC recurrence after liver resections [ 22 ]; recently, there were few studies that addressed the association between lipid profiles and the outcome of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, abnormal lipid and lipoprotein levels were considered to be related with the incidence and development of several types of cancer[ 13 , 14 ]. Several researches showed that elevated TG level and suppressed high-density lipoprotein cholesterol (HDLc) level were related to a high risk of occurrence and death in colon, breast, lung, and prostate cancers[ 15 18 ]. However, the relationships between blood profile and liver cancer were contradictory due to the complex etiology.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies reveal a new relationship between blood lipids and the risk of the most common cancer entities. For example, low levels of serum lipids is positively associated with cancer and its mortality [ 13 , 14 , 17 ]. High level of TC or HDL is associated with a reduction of cancer mortality [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Se trata de la presencia de un conjunto de factores de riesgo presentes en un individuo, que actúan como factores independientes (1,2). Se caracteriza por la aparición, en forma simultánea o secuencial, de diversas alteraciones metabólicas e inflamatorias a escala molecular, celular o hemodinámico asociadas con alteraciones en el metabolismo glucídico -Diabetes mellitus Tipo 2 (dm2), tolerancia alterada a la glucosa o glucemia alterada en ayunas-, resistencia a la insulina, obesidad central, dislipidemia e hipertensión (3)(4)(5). No solo es una realidad clínica entre prácticamente todos los grupos étnicos, raciales y geográficos, sino que constituye un problema de salud evidente, tanto por su alta prevalencia, como por su papel como factor de riesgo de otras enfermedades que implican una gran morbimortalidad, como son las enfermedades cardiovasculares y la diabetes mellitus, para las cuales eleva en 2 y 5 veces, respectivamente, el riesgo de padecerlas (6).…”
Section: Introductionunclassified